以藝術本位教育探索文化回應氣候變遷： 創作《地下部落》的表演個案研究 Exploring Cultural Responses to Climate Change Through Arts-Based Education: A Performance Case Study of “Swadriadringi” - 鄧宗聖 Tzong-Sheng Deng; 王慧蘭 Hui-Lan Wang (臺灣教育社會學研究)
本研究旨在以藝術本位教育的觀點，以屏東縣瑪家鄉的北葉國小為創作實踐的教育場域，將「氣候變遷」作為探索概念，建構原住民族族語戲劇《地下部落》，研究者主動參與作品發展的形成歷程並做紀錄，藉此分析作品如何再現的文化信念與知識。研究者以知識社會學的角度探討建構氣候知識的文化特質，進而闡述藝術本位教育的知識爭論，最後探討文化回應的特質，以及與藝術實踐的關係，作為詮釋基礎。研究方法取徑藝術本位研究觀點，透過參與觀察口述文本發展到舞臺表演的歷程蒐集研究資料，與學校教師、學生在排演過程中創造情節、對話與行動，透過記錄與討論建立表演內容，並將劇本作為內容分析文本，從氣候事件作為開端，分析情節中的對話與行動，如何形構原住民族知識。研究發現，原住民族知識生產考慮到未知與已知之間的關聯，亦即《地下部落》連結了過去（部落精神）、現在（氣候事件）和未來（禁忌與儀式），從資源匱乏、探尋資源、建立部落關係和作物多樣性等四段情節中建構情境，再以互助、探尋、分享與儀式等行動作為知識再生產的策略，歸納並形構出倫理與自然資源管理、祭儀與水源土地關係等知識類型，用以回應自然環境變化而發展出與自然共生的關係性知識。 This study implements creative practices in the educational setting of Beiye Elementary School in Majia Township, Pingtung County. Using “climate change” as an exploratory concept, the study develops an indigenous language drama titled “Swadriadringi” through an arts-based educational approach. The researcher actively participated in and documented the development of the drama to analyze how cultural beliefs and knowledge are represented through the work. Through the lens of the sociology of knowledge, the researcher analyzes the cultural characteristics of climate knowledge construction, clarifies the knowledge discourse in artsbased education, and examines the characteristic of cultural responsiveness and its relationship to artistic practice, providing a foundation for interpretation. The study employs an arts-based research methodology. Data were collected through participant observation of the process from oral text development to stage performance. Teachers and students collaboratively created plot elements, dialogues, and actions during the rehearsal process. Performance content was established through documentation and discussion, with the script serving as a text for content analysis. Beginning with climate events, the analysis examines how dialogues and actions within the narrative construct indigenous knowledge. The findings reveal that indigenous knowledge production involves a relationship between the known and the unknown. “Swadriadringi” connects the past (tribal spirit), present (climatic events), and future (taboos and rituals). The narrative constructs scenarios through four episodes: resource scarcity, resource seeking, establishment of tribal relationships, and crop diversity. Knowledge reproduction strategies include mutual assistance, exploration, sharing, and rituals, which synthesize and form knowledge types such as ethics and natural resource management.